Las inmisiones de ozono en la ciudad de Zaragoza, período 2002-2008 - Matute-Najarro, Rosa; González-Hidalgo, José Carlos (Geographicalia, 2014)
Ozone concentration during 2002-2008 has been analyzed in Zaragoza. Interannual evolution shows the summer maximum-winter minimum pattern, and ozone inmission increased during the study period. Daily calendar shows daytime-nightime differences, accentuated in summer. Weekly daily values show the week-end effect. Ozone concentrations never reach the legal threshold. It can be said that ozone is not a pollutant dangerous in Zaragoza.